Pre-exposure prophylaxis among Brazilian men who have sex with men: a comparative study between migrants and non-migrants - Sousa, Álvaro Francisco Lopes; Lima, Shirley Verônica Melo Almeida; Ribeiro, Caíque Jordan Nunes; de Sousa, Anderson Reis; Camargo, Emerson Lucas Silva; de Oliveira, Layze Braz; Neto, João Cruz; Fronteira, Inês; Mendes, Isabel Amélia Costa (Frontiers in Public Health, 2023)
Introduction Investigating the use and adherence to pre-exposure prophylaxis (PrEP) in MSM is a global health priority in the fight against HIV. Strategies must be capable of increasing usage and reaching not only the population living in the country but also those who immigrate, who face additional vulnerabilities. Based on this, in this observational, cross-sectional, and analytical study, our aim is to analyze the use of PrEP among Brazilian men who have sex with men, whether they are migrants or not. We aim to highlight preventive opportunities and strategies for the global health scenario. Methods We utilized a sample of Brazilians living in the country and Brazilian immigrants residing in Portugal, one of the main destinations for Brazilians in recent years. To estimate the prevalence ratio (PR) of PrEP use, we employed the Poisson regression model with robust variance estimation using a covariance matrix. Results A total of 1,117 Brazilian MSM PrEP users participated in this study, with 788 residing in Brazil and 328 in Portugal. Multivariate analysis was conducted in three stages: overall, and for subgroups of residents in Brazil and immigrants in Portugal. We identified four convergent factors that increased the prevalence of PrEP use in Brazilians regardless of migration status: having two or more casual sexual partners per month, engaging in challenging sexual practices as the receptive partner, disclosing serological status on apps, and being single. Among native Brazilians, four unique factors stood out: being in a polyamorous relationship, having sexual relations with unknown casual partners, and having higher levels of education. Discussion This study highlights the need to implement strategies to strengthen PrEP adherence in Brazil and create international programs that facilitate its usage among populations migrating between these two countries.